О пассивных и активных алгоритмах восстановления функций - Корнейчук, Н.П. (Український математичний журнал, 1993)
Розглядаються пасивні та активні алгоритми відновлення функцій, які задовольняють умову |f(t')−f(t'')| ≤ |t'−t''|^α,0 < α ≤ 1, за значеннями f(t) в точках відрізка [a,b]. Запропонований активний алгоритм, який при 0 < α < 1 для монотонних функцій вказаного класу гарантує порядок похибки в C[a,b] більш високий, ніж будь-який пасивний алгоритм. We consider passive and active algorithms of reconstruction of functions, satisfying the condition |f(t')−f(t'')| ≤ |t'−t''|^α, 0 < α ≤ 1, according to their values f(t) at the points of the interval [a,b]. An active algorithm is presented which guarantees, for monotonic functions from the above-mentioned class with 0 < α < 1, a higher order of error in C[a,b] than can be attained by any passive algorithm.